Surface‐Group‐Oriented, Condensation Cyclization‐Driven, Nitrogen‐Doping Strategy for the Preparation of a Nitrogen‐Species‐Tunable, Carbon‐Material‐Supported Pd Catalyst. Issue 1 (24th January 2019) - Lu, Chunshan; Zhang, Xuejie; Qi, Yani; Ji, Haoke; Zhu, Qianwen; Wang, Hao; Zhou, Yebin; Feng, Zhenlong; Li, Xiaonian
Abstract: A nitrogen‐carbon framework with the thickness of several molecules was fabricated through a straightforward nitrogen‐doping strategy, in which specially designed surface‐oxygen‐containing groups (SOGs) first introduced onto the porous carbon support were used to guide the generation of a surface‐nitrogen‐containing structure through condensation reactions between SOGs and the amidogen group of organic amines under hydrothermal conditions. The results indicate that different kinds of SOGs generate different types and abundances of N species. The CO‐releasing groups are apt to form a high proportion of amino groups, whereas the CO2 ‐releasing groups, especially carboxyl and lactones, are mainly transformed into pyrrolic‐type nitrogen. In the framework with dominant pyrrolic‐type nitrogen, an electron‐rich Pd activated site composed of Pd, pyrrolic‐type N and C is built, in which electron transfer occurs from N to C and Pd atoms. This activated site contributes to the formation of electron‐rich activated hydrogen and desorption of p‐chloroaniline, which work together to achieve the superior selectivity about 99.90 % of p‐chloroaniline and the excellent reusable performance. This strategy not only provides low‐cost, nitrogen‐doped carbon materials, but also develops a new method for the fabrication of different kinds of nitrogen species structures. Abstract : On the surface : The surface‐group‐oriented nitrogen‐doping strategy for activated carbon‐supported Pd catalysts and the potential selective hydrogenation mechanism of p‐chloronitrobenzene are presented.